Pressure Drop Distribution in Smooth and Rib Roughened Square Channel with Sharp 180° Bend in the Presence of Guide Vanes - Venkata Ratna Rao.D; S. V. Prabhu (International Journal of Rotating Machinery)
An experimental investigation is carried out to study the effect of several turn treatments like single guide vane (short and long) and multiple guide vanes on the pressure drop distribution in smooth and rib roughened square channels with a sharp 180° bend. The sharp 180° turn is obtained by dividing a rectangular passage into two square channels using a divider wall with a rounded tip at the location where the flow negotiates the turn. In rib roughened channels, ribs are configured on the top and bottom surfaces in a symmetric arrangement with an angle of 90° to the mainstream flow. Rib height-to-hydraulic diameter ratio (e/D) is maintained constant at 0.14 with a constant pitch-to-rib height ratio (P/e) of 10. The pressure drop distribution normalized with the mainstream fluid dynamic pressure head is presented for the outer surfaces. Results suggest that 90° multiple guide vanes result in the decrease of overall pressure drop by around 40% in smooth square channels. However, a reduction in overall pressure drop by only 15% is achievable through guide vanes in rib roughened square channels.